Justice in the digital state : assessing the next revolution in administrative justice - Tomlinson, Joe (Policy Press, 2019)
Exploring how justice is delivered at a time of rapid technological transformation, Justice in the Digital State exposes urgent issues surrounding the modernization of courts and tribunals. This cutting-edge research offers an authoritative and much-needed guide for navigating through the challenges of digital disruption.
Keywords: Justice, Administration of -- Great Britain.; Justice, Administration of -- Technological innovations -- Great Britain.; Technology and law.; Technologie et droit.; Constitutional & administrative law.; Justice, Administration of -- Technological innovations.; Justice, Administration of.; Law.; Great Britain.; Electronic books.